ANALISIS KESALAHAN EYD PADA MEDIA MASSA - Alandra Adzralya (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
Writing in accordance with the Enhanced Spelling (EYD) is an important aspect in journalism to ensure the clarity and credibility of the information conveyed. However, various mass media still often make mistakes in applying standard Indonesian language rules. This research aims to analyze EYD errors found in various mass media, both print and online. The method used in this research is descriptive qualitative analysis with a case study approach to a number of news articles from various sources. The results show that the most common errors found include the use of inappropriate punctuation, errors in writing standard and non-standard words, and the use of ineffective sentences. These findings emphasize the importance of increasing awareness and understanding of EYD rules among journalists and editors to improve the quality of language in the news.